Evaluation of the polyhedral mesh style for predicting aerosol deposition in representative models of the conducting airways. (January 2022) - Thomas, Morgan L.; Longest, P. Worth
Abstract: A critical factor affecting the accuracy of Computational Fluid Dynamic (CFD) simulations and the time required to conduct them is construction of the computational mesh. This study aimed to evaluate the relatively new polyhedral mesh style for simulating aerosol deposition in the upper conducting airways compared with established meshing techniques and experimental data. Hexahedral and polyhedral mesh solutions were compared in two benchmark geometries: 1) a 90°-bend with flow characteristics similar to the extrathoracic airways of an adolescent child, and 2) a double bifurcation representing bifurcations B3–B5 in an adult. Both 4-block and 5-block hexahedral meshes were used in the 90°-bend to capture the potential of fully-structured hexahedral meshes. In the 90°-bend, polyhedral elements matched polydisperse in vitro deposition data with 20% relative error (RE; averaged across the particle sizes considered), which is an improvement on the accuracy of the 4-block hexahedral mesh (35% RE) and is similar to the accuracy of the 5-block hexahedral mesh (19% RE). In the double bifurcation, deposition fraction relative differences evaluated between polyhedral and hexahedral meshes ranged from 0.3% to 28.6% for the different particle sizes assessed, which is an order of magnitude improvement compared with previous studies that considered hexahedral vs. hybrid tetrahedral-prism meshes for the same flow field. Solution convergence time with polyhedral elements was found to be 50%–140% higher than with hexahedral meshes of comparable size. While application dependent, the increase in simulation time observed with polyhedral meshes will likely be outweighed by the ease and convenience of polyhedral mesh construction. It was concluded that the polyhedral mesh style, with sufficient resolution especially near the walls, is an excellent alternative to the highly regarded hexahedral mesh style for predicting upper airway aerosol transport and deposition, providing a powerful new tool for the assessment of respiratory aerosol dosimetry. Graphical abstract: Image 1 Highlights: Hexahedral meshes offer high accuracy but are difficult to construct. Polyhedral mesh building may be automated, but hexahedral mesh comparison is needed. Polyhedral meshes can match total and local aerosol deposition of hexahedral meshes. Solution convergence time is 50%–140% longer for polyhedral vs. hexahedral meshes. Polyhedral meshes are an acceptable approach in computational pulmonary aerosol research.